Optimal Portfolio Selection Using the Single Index Method on LQ45 Shares in the Banking Sector - Widya Novita Sari; Dita Fitriani; Indri Widya Wulandari; Maria Yovita R Pandin (Finance : International Journal of Management Finance, 2023)
The purpose of this study is to determine the proportion of each stock that makes up the optimal portfolio so that it is easier for investors to determine which company has the optimal portfolio. The population that is the focus of this study refers to stocks belonging to the LQ45 index in the banking sector during the 2021-2023 period, namely 7 stocks. The sampling method is carried out by applying a purpose sampling technique, which results in 5 stocks that qualify according to the criteria of this study. The data used is secondary data derived from monthly stock prices. From the research results, all stocks showed positive returns, with BBRI having the highest return. In addition, the analysis results show that using the single index model approach, the stocks of the LQ45 Index members in the banking sector in the period August 2021 to July 2023 show that 4 out of 5 stocks (BBRI, BMRI, BBCA, and BBNI) form an optimal portfolio. Meanwhile, BBTN shares cannot be said to be an optimal portfolio because ERBi is smaller than Ci.